AB0911 Characteristics of PFAPA Patients Responding to Colchicine Treatment: A Retrospective Study of 21 Children. (10th June 2014) - Dusser, P.; Neven, B.; Hentgen, V.; Koné-Paut, I.
Abstract : Background: Colchicine is an alkaloid that has been used for years in familial Mediterranean fever (FMF), a hereditary autoinflammatory disease associated with excessive IL-1 (interleukine 1) signaling. It has also been used as prophylaxis for patient with frequent PFAPA (periodic fever, aphthous stomatitis, pharyngitis, adenopathy) episodes. PFAPA syndrome is characterized by sudden attacks of fever associated with aphthous stomatitis, pharyngitis and adenopathy occurring every 3-8 weeks and lasting for 3-6 days. It usually begins at the age of 4 years old. The physiopathology of this disease is not well known but a major role of an excessive IL-1 signaling has been suggested by Stojanov in 2011 allowing to think of a potential role of the colchicine in the therapeutic arsenal. Objectives: To study the characteristics of PFAPA population in which colchicine treatment allows a decrease of the PFAPA attacks recurrences. This could allow us to defining predictive factors of a potential response to colchicine treatment. Methods: A retrospective and multicentered study was performed on PFAPA patients under colchicine prophylaxis treatment. Two groups were studied depending on their colchicine's response. A good colchicine response was defined as a rise of 50% or more of the time between two attacks. Subgroup analysis was performed using Mann-Whitney test regarding the family history, the age at onset, the recurrence and the characteristics of the attacks (duration and maximum fever, asthenia, pharyngitis, aphtous stomatitis, lymphadenopathy, abdominal pain) and the genetic background of the patient namely heterozygous for the Familial Mediterranean fever gene. Results: Twenty one children were studied. Among them, 67% were male. The mean age at onset of PFAPA disease was of 2.1±1.4 years old. The PFAPA attacks in our population was described as a 3.1±1.1 days (mean, standard deviation) (1 to 7 days) of strong fever (mean 39°C) with chills (28%) most frequently associated with pharyngitis (78%), abdominal pain (75%), cervical adenitis (62%), asthenia (50%) and aphtous stomatitis (47%). Looking at genetics, 52% (11/21) of the patients were FMF heterozygous. Twelve patients were defined as responder to colchicine. No significant differences were found between the two groups. Conclusions: Future prospective studies should be performed using a larger group of patients in order to better define the efficiency of the colchicine and its indications in PFAPA patients. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.6041